Shirvanis’ Role in the Ottoman Thinking and Science Sadraddinzades, An Ulema Dynasty in the 17th and 18th Centuries Ottoman State - Mammadova, Khalida (Scholarya Demo Journal of Ruby, 2020)
Sadraddinzades, one of the scholar dynasties that lived in the Ottoman empire in the 16-18th centuries, was prominent and raised scholars, mudarrises (teachers), qazis (war veterans), sheikhs in their times. The enlightenment tradition started by Muhammad Amin ibn Sadraddin Mollazade al-Shirwani, was maintained by his son Muhammad Amin Sadraddinzade al-Shirvani and his sons and grandchildren’s (Rohullah Mehmed Efendi, Nimetullah Efendi, Feyzullah ibn Muhammad Amin, Sadik ibn Feyzullah ibn Muhammad alKonstantini al-Shirwani, Mektubi Abdurrahman Efendi, Kassam Mehmed Efendi, Telhisi Mustafa Efendi). Although there are significant studies in Turkey about some of the scholars mentioned above, the lives and works of many of them have not been researched substantially. Nevertheless, during the analysis of the studies that mention the name of Sadraddinzade, it is revealed that these people have been mixed up with one another. This situation is a major obstacle for researchers working on this subject that hinders the collection of accurate information about Sadraddinzades. This article provides chronologically organized information about the life and works of several scholars from Shirvan, who had a significant place in the scholarly life of the Ottoman state in the 16-18th centuries, worked in various fields of the state and were originally from Shirvan. We hope that this article will the deficiencies in previous studies on the subject and contribute to future research.